(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
تمّ في هذا البحث دراسة تبعثر حزمة جسيمات نقطية منخفضة الطاقة ، واردة على هدف كرويّ صلب باستخدام نظريتي التبعثر الكلاسيكية ،والكميّة في مجال الطاقات المنخفضة, حيث تبيّن لنا أن هناك تبايناً طفيفاً بين المفهومين السّابقين، يتمثل في كون مقطع التبعثر الكمي يساوي أربعة أمثال مقطع التبعثر الكلاسيكي أي: . In this research has been studied scattering of pointparticles beam with low energy coming on hard spherical target by using theory ofclassical and quantum scattering In the field of low-energy, We show the existence of a slight discrepancy between them,which is in fact a quantumcross section of scattering equals four timesthe classical Cross-section: .